Development of Multi Field Software Solutions and their Application for the Optimization of Electromagnetic High Speed Forming processes - Blum, H.; Stiemer, M.; Suttmeier, F. T.; Svendsen, B.; Unger, J. (Institut für Umformtechnik - Technische Universität Dortmund, 2004)
The simulation of complex processes in engineering solids involving coupled mechanical and non-mechanical fields represents a challenge to physicists, mathematicians, and engineers. Both, the formulation of such models and their numerical implementation involve a great number of difficulties. Electromagnetic forming is one example of such a process, whose modelling and simulation requires a coupled electromagnetic-thermomechanical model. The purpose of this contribution is to discuss some key issues associated with the modelling and simulation of electromagnetic metal forming (EF) and the corresponding development of a finite-element-based simulation tool for EF. In particular, the modelling is based on a thermodynamically-consistent electromagnetic-thermoelastoviscoplastic material and field model in which the energy and momentum balance are coupled to the quasi-static form of Maxwell s equations via the electromotive intensity and Lorentz force, respectively. On the algorithmic side, questions like the choice of meshes, the element formulation, the numerical treatment of nonlinearities, possible model simplifications, different discretisation strategies, realisation of the non-linear coupling etc. are discussed for the presented software solution. Such issues are investigated with the help of benchmark simulations that have been developed for this purpose. Finally, as an example of an application of the developed software tool, a computer aided manufacturing (CAM) problem is considered. Here, the size of the tool coil and the peak value of the current in the tool coil circuit are optimised in order to achieve the prescribed work-piece form within the given tolerance.
Keywords: electromagnetic metal forming; modeling; viscoplasticity; 620; 670